2015
DOI: 10.1097/md.0000000000001113
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Liver Metastases From Gastric Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…Thus far, many investigators have agreed that age, histological type, N-stage and radiation status were independent prognostic factors [16, 17, 18, 19, 20, 21]. In our study, using a multivariate analysis, we arrived at the same conclusions and found that surgery was an additional independent prognostic factor.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Thus far, many investigators have agreed that age, histological type, N-stage and radiation status were independent prognostic factors [16, 17, 18, 19, 20, 21]. In our study, using a multivariate analysis, we arrived at the same conclusions and found that surgery was an additional independent prognostic factor.…”
Section: Discussionsupporting
confidence: 81%
“…Although systemic chemotherapy is the standard treatment strategy, the MST of these patients is only approximately 12 months, and long-term survival beyond 5 years is rare [14, 15]. Recently, it was reported that in selected cases, especially in patients with gastric cancer with liver metastases, aggressive surgical treatment may lead to unexpected results [16, 17, 18, 19, 20]. In a review based on 19 studies, Kerkar et al reported that the 5-year survival rate of gastric cancer patients with liver metastases who underwent liver resection was 26.5% (range: 0-60%) [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, other publications [35,36] and results obtained by our clinic (although they concern a small group of patients, as in other single liver surgery centers) indicate that in some patients (single metachronous metastasis, no extrahepatic lesions, no peritoneal lesions, with subsequent chemotherapy) liver resection due to gastric cancer metastases offers a better chance of survival than just chemotherapy.…”
Section: Discussionsupporting
confidence: 58%